2022
DOI: 10.1021/acs.chemmater.2c00418
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of Porous Crystals from Ion-Paired Prenucleation Clusters

Abstract: Current nucleation models propose manifold options for the formation of crystalline materials. Exploring and distinguishing between different crystallization pathways on the molecular level however remain a challenge, especially for complex porous materials. These usually consist of large unit cells with an ordered framework and pore components and often nucleate in complex, multiphasic synthesis media, restricting in-depth characterization. This work shows how aluminosilicate speciation during crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
59
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(64 citation statements)
references
References 58 publications
5
59
0
Order By: Relevance
“…Liquid-state 27 Al NMR measurements have shown that the aluminate speciation in HSIL synthesis liquids exclusively consists of small aluminosilicate oligomers, and zeolites crystallize from these liquids upon the supersaturation of specific aluminosilicate oligomers. 20 Therefore, it is possible to rationalize our observations by considerations of aluminosilicate solution chemistry. 1,69 Increasing chemical activity of hydroxide promotes depolymerization of aluminosilicates via deprotonation and hydrolysis, increasing the oligomer charge density and stabilizing oligomers of low nuclearity, including the Al-containing species.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Liquid-state 27 Al NMR measurements have shown that the aluminate speciation in HSIL synthesis liquids exclusively consists of small aluminosilicate oligomers, and zeolites crystallize from these liquids upon the supersaturation of specific aluminosilicate oligomers. 20 Therefore, it is possible to rationalize our observations by considerations of aluminosilicate solution chemistry. 1,69 Increasing chemical activity of hydroxide promotes depolymerization of aluminosilicates via deprotonation and hydrolysis, increasing the oligomer charge density and stabilizing oligomers of low nuclearity, including the Al-containing species.…”
Section: Discussionmentioning
confidence: 77%
“…At room temperature, upon the addition of aluminate, all mixtures with [SiO 2 ]/[MOH] < 0.5 and [H 2 O]/[MOH] < 15 form monophasic, optically clear liquids. 20 This region, characterized by high alkalinity and low water content, yields hypo-hydrated ionic liquids. 17 , 20 In these liquids, high charge density stabilizes aluminum in small aluminosilicate oligomers through intimate interactions with alkali cations, leading to aluminate solubility much higher than previously predicted by aluminosilicate speciation models, 12 , 20 23 similar as observed for the increased solubility of gibbsite in concentrated electrolytes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations